Are children with mitral valve prolapse more anxious? - Meryem Beyazal; Utku Arman Orun; Ilker Ufuk Sayici (Wolters Kluwer Medknow Publications, 2023)
Background : Mitral valve prolapse (MVP) is a common valvular disease in children. Symptoms in children with MVP are not explained by the severity of mitral regurgitation alone. Hence, we sought to correlate symptom status with the incidence of anxiety disorder in this population. Materials and Methods : Groups were as follows: (a) MVP; n = 115; mean age: 13.5 ± 3.06 years and (b) control; n = 53; mean age: 15.1 ± 13.2. The Screen for Child Anxiety-Related Emotional Disorders (SCAREDs) scale was filled by all participants. The SCARED scores of 25 and above determined a warning for anxiety disorders. Results : The mean SCARED scale values of MVP and control groups were 29.2 ± 13.08 and 24.9 ± 14.17, respectively (P = 0.065). Although the SCARED scale score was higher among the MVP patients, no significant difference was found between the groups in terms of the mean SCARED score, or the number of participants with a score of 25 or more. While girls with MVP had higher anxiety scores compared to boys with the disorder, there was no difference with respect to SCARED scores in children with MVP and the general population when analyzed separately by gender. Moreover, the SCARED scale score was significantly higher in symptomatic MVP patients than in asymptomatic cases. Conclusion : Children with MVP did not have higher anxiety scores compared to those without the syndrome. However, MVP patients with higher anxiety scores may benefit from a psychiatric assessment since higher scores correlate with symptoms.